2020
DOI: 10.17116/oftalma2020136052226
|View full text |Cite
|
Sign up to set email alerts
|

On the question of progressive hyperopia correction after radial keratotomy

Abstract: Механизм формирования прогрессирующей гиперметропии в отдаленные сроки после проведения радиальной кератотомии (РК) связан с хирургическим воздействием, индивидуальными биомеханическими особенностями фиброзной оболочки глаза и их возрастными изменениями, а также нарушениями гидродинамики. При выборе метода коррекции прогрессирующей гиперметропии необходимо учитывать ряд особенностей этого вида индуцированных рефракционных нарушений: нестабильность и иррегулярность рефракции, сочетание с пресбиопией, возможност… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…1,2 Although patients with RK do not represent most individuals studied, some complications related to the SCL wear have been reported. 8–10 In our study, the first case of ocular perforation was reported in a late postoperative period of radial keratotomy wearing SCL.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…1,2 Although patients with RK do not represent most individuals studied, some complications related to the SCL wear have been reported. 8–10 In our study, the first case of ocular perforation was reported in a late postoperative period of radial keratotomy wearing SCL.…”
Section: Discussionmentioning
confidence: 56%
“…6,7 In our case, the perforation occurred 26 years after the RK surgery, which may show us that corneal instability can increase as time passes, with microtrauma, such as eye scratching, constant eyelid movement in the blinking motion, and in the case of contact lens wear, through the daily manipulation of placing and removing these lenses. 10 Another factor that may have facilitated the perforation in the reported case was the other two previous refractive surgeries performed on the same eye, which made the cornea thinner and more susceptible to changes.…”
Section: Discussionmentioning
confidence: 86%